Pendidikan Kesehatan Latihan Range Of Motion Aktif dan Pasif - Rino M; Jufri Al Fajri (Jurnal Abdimas Kesehatan (JAK), 2021)
In Indonesia, the number of fracture surgeries by the end of 2017 had reached 27.9% of the total types of surgery. The prevalence of fractures is quite high, namely the incidence of fractures in the extremities which is around 46.2%. Non-pharmacological management is physiotherapy to reduce pain, maintain, increase muscle and joint strength with Range of Motion (ROM). This community service aims for patients and families to know and understand about active and passive ROM movements. Extension methods using demonstrations, lectures and leaflets. This community service is followed by families and patients who experience mobility barriers due to fractures who have returned home at the Muara Kumpeh Health Center area. The time of service was carried out in July 2020 with a total of 15 people. The results of this community service after the team carried out community service activities, patients and families who attended began to understand and understand how to move ROM in the lower extremities